Research hotspots and frontiers of alcohol and epilepsy: A bibliometric analysis - Wenhui Liu; Huan Li; Simei Lin (Wiley, 2024)
Abstract Purpose Alcohol is implicated in epileptogenesis and seizures attack. An increasing number of studies about alcohol and epilepsy have been published. We aimed to assess research trends and hot spots in the field of alcohol and epilepsy. Patients and Methods Literature concerning alcohol and epilepsy was systemically searched through the Web of Science database. Collaborative maps were quantitatively analyzed by using the VOSviewer and CiteSpace tools. Results A total of 1578 papers about the field of alcohol and epilepsy were taken into analysis, which was written by 6840 authors from 2153 institutions in 85 countries, published in 676 journals, and cited 79 667 references from 10 750 journals. The United States was the leading country and had close ties with others. The University of Toronto was the most productive institution. Alcoholism‐clinical and experimental research was the fastest‐growing journal. Richard J. Bodnar was the author contributing the most literature. Analysis of keywords showed epilepsy, alcohol, seizures, alcohol withdrawal, and management were common themes. Conclusion The presented study conducted the first bibliometric analysis of the field of alcohol and epilepsy, which will provide insights into the latest progress, evolution paths, frontier research hot spots, and future research trends in the field.